Psycho-social and spiritual backgrounds, experiences, and needs as a transsexual: a qualitative study within Persatuan Insaf Pahang - Draman, Samsul; Suofeiya, Maliya; A., Liyana; S., Farhani; R., Jannah; Mohd Rus, Razman (International Islamic University Malaysia, 2016)
Transsexuals face discriminations and rejections from the Malaysian society. The number of studies done on understanding the phenomenology, experiences, and problems faced by transsexuals is still few in Malaysia. This research aims to document their psycho-social and spiritual backgrounds and the relevant experiences, and to explore their perceptions and needs as male-to-female transsexuals in the context of Persatuan Insaf Pahang, Malaysia. Materials and Methods: A qualitative research was carried out in July and August 2015 among eight male-to-female transsexual adults in Kuantan, Pahang. Snowball sampling was used. Participants who gave consent were interviewed in two focus groups. Data obtained was transcribed and used as the primary data source. Results: Subjects in this study reported confusions over their gender identity since childhood. They struggled against conflicts regarding their transsexuality in adolescence, and eventually many quit their studies. As adults, they were discriminated against in employment and religious settings. They provided positive feedbacks on religious authorities who could understand problems unique to transsexuals and empathise with the transsexual community. Conclusion: The psycho-sexual phenomenology is the same in transsexuals all over the world. Misunderstanding and discrimination from the society remain heavy towards this community. Transsexuals should learn to adapt to meeting expectations from the society as well, so they could be accepted in public. They will need religious guidance and spiritual support for better quality of life. Dedicated efforts are still needed in training professionals in the educational, medical, and religious fields to attend to the specific needs of transsexuals in this country.